Membedah Al-Kashsha - Abdul Syukkur (El-Furqania : Jurnal Ushuluddin dan Ilmu-Ilmu Keislaman, 2021)
The difference in opinion between Ahlus sunnah wal jamaah and Muktazilah has reached the point of misleading one another. Thus, reference sources for one sect will not be used as a reference for other sects, but this is not the case with al-Kashsha>f which is the work of Muktazilah which is the reference for the ulama-Ahlussunnah wal Jamaah. This article examines the book al-Kashsha>f by al-Zamakhshari> al-Mu'tazili>, its writing background, the biography of the author, the characteristics of the book al-Kashsha>f, its advantages and disadvantages, the interpretation which is the point of criticism of Ahlussunnah wal Jamaah, and Appreciation of Ulama Ahlussunnah wal Jamaah for al-Kashsha>f. Keywords: Al-Kashsha>f, al-Zamakhshari>, Muktazilah, Ahlussunnah wal Jamaah.